Serum surfactant protein-D as an early marker of pulmonary dysfunction in type 2 diabetic patients - Zahid, Hira; Zulfiqar, Sibgha (Journal of the Pakistan Medical Association, 2026)
Objectives: To investigate the role of surfactant protein D as an early biomarker for diabetic complications. Method: The cross-sectional study was conducted at the diabetic clinic of Sheikh Zayed Hospital, Lahore, Pakistan, from March 1 to August 31, 2021, and comprised type 2 diabetic patients and non-diabetic controls. Serum surfactant protein D levels were measured using enzyme-linked immunosorbent assay, and pulmonary function was assessed using spirometry. Data analysed was conducted using SPSS 26. Results: Of the 164 subjects, 82(50%) each were diabetics and controls. In both the groups, there were 49(59.75%) females and 33(40.24%) males. The mean age of diabetics was 51.02±11.98 years, while it was 44.65±15.18 years among the controls (p<0.05). Diabetics had significantly elevated surfactant protein D levels (63.59±26.20ng/mL) compared to non-diabetics (37.41±23.65ng/mL; p<0.05) as shown in Table 2. Pulmonary function was also compromised in diabetics, with lower forced expiratory volume in one second and its ratio with forced vital capacity (p<0.05) despite similar forced vital capacity values (p<0.05). Conclusion: Increased levels of serum surfactant protein D were found to be linked with pulmonary dysfunction. Surfactant protein D could serve as an early indicator of pulmonary involvement in diabetes. Key Words: Diabetes mellitus type 2, Surfactant protein D, Pulmonary function tests, Spirometry, Lung diseases, Oxidative stress.